Enhanced surgical outcomes in refractory glaucoma: a retrospective study of using adjustable sutures with Ex-PRESS filtration device - Ji, Zhen; Wei, Dongdong; Yu, Na; Yang, Xiaolan (Frontiers in Medicine, 2025)
PurposeEvaluate the clinical efficacy of combining adjustable sutures with the Ex-PRESS Glaucoma Filtration Device in patients with refractory glaucoma, with an emphasis on controlling intraocular pressure (IOP) and reducing postoperative complications.MethodsThis retrospective cohort study involved refractory glaucoma patients treated at Jinan Second People’s Hospital between January 2023 and October 2024. Patients were divided into two groups: one received standard Ex-PRESS implantation (control), and the other received Ex-PRESS implantation with adjustable sutures (experimental). Outcomes included IOP, best-corrected visual acuity (BCVA), filtering bleb morphology, and postoperative complications, assessed over a 6-month follow-up.ResultsThe two groups included 75 patients (75 eyes), with 38 (38 eyes) in the experimental group and 37 (37 eyes) in the control group. Both groups showed significant postoperative IOP reduction. The experimental group had higher IOP on Day 1 but significantly lower IOP at all subsequent time points (Week 1 to 6 months, P < 0.001). The experimental group had a higher ratio of functioning blebs (84.21% vs. 62.16%, P = 0.031) and lower complication rates (5.26% vs. 24.32%, P = 0.020). At 6 months after the operation, the two groups did not differ in terms of BCVA (χ2 = 2.787, P = 0.248). Some complications in the control group (device obstruction and malignant glaucoma) required additional surgical interventions. No cases of endophthalmitis occurred in either group.ConclusionThe addition of adjustable sutures to Ex-PRESS implantation offers superior IOP control, promotes the formation of functioning bleb, and reduces postoperative complications in refractory glaucoma. This technique provides a promising refinement to existing surgical strategies. Further prospective studies are warranted to confirm long-term benefits.